An Entropy Based Anomaly Traffic Detection Approach in SDN - Mingxin Wang; Huachun Zhou; Jia Chen; Hongke Zhang (Dianxin kexue)
SDN（software defined networking）is a novel network infrastructure which separate the control plane from the data plane. Taking advantage of the idea of SDN, a central security center was built which collected traffic from the SDN data plane entity for analyzing. The attacks can be detected based on the entropy variation of the identifier and locate the type of attack with the classification algorithm. As the anomaly patterns were detected, the security center would cooperate with the central controller to install the flow table to alleviate the influence of the attack. The anomaly traffic can be detected early and can't influence the performance of the controller. Besides, the controller can be protected from attack based on our system.